Puerarin Attenuates Diabetic Nephropathy by Promoting Autophagy in Podocytes - Li, Xueling; Zhu, Qingqing; Zheng, Rong; Yan, Jiayi; Wei, Minggang; Fan, Yichen; Deng, Yueyi; Zhong, Yifei (Frontiers in Physiology, 2020)
Puerarin, an active compound of radix puerariae, is a major compound used in Chinese herbal medicines to treat patients with diabetic nephropathy (DN). In the previous studies, we showed that puerarin exerts renoprotective effects in Streptozocin (STZ)-induced diabetic mice through activation of Sirt1 and anti-oxidative effects. Here, we further investigated the underlying mechanism mediating the renal protective effects of puerarin in DN. We studied the effects and mechanism of puerarin in STZ-induced diabetic mice and in cultured immortalized mouse podocytes treated with high glucose. We confirmed that puerarin ameliorated urinary albumin creatinine ratio and kidney injury in STZ-induced DN mice. We found that expression of heme oxygenase 1 (HMOX-1) and Sirt1 was suppressed in diabetic glomeruli but restored by puerarin treatment at both mRNA and protein levels. Additionally, we found that puerarin induced autophagy in the kidney of DN mice. In conditionally immortalized mouse podocytes, puerarin inhibited HG-induced apoptosis and restored the mRNA and protein levels of HMOX-1 and Sirt1. Interestingly, we showed that puerarin decreased liver kinase B1 (LKB1) acetylation, thereby promoting adenosine 5‘-monophosphate-activated protein kinase (AMPK)-dependent autophagy. Knockdown of HMOX-1 and Sirt1 expression or treatment with the autophagy inhibitor 3-methyladenine abolished the protective effects of puerarin in HG-treated podocytes. Taken together, these results suggest that puerarin protects podocytes from diabetes-induced injury through HMOX1 and Sirt1-mediated upregulation of autophagy, a novel mechanism explaining its renal protective effects in DN.